Preventing Legionellosis - McCoy, William F. (IWA Pub., 2005)
Preventing Legionellosis covers the biology of Legionella and presents a comprehensive review of best practices for legionellosis prevention from around the world. Recent outbreaks, climbing incidence rates and pending lawsuits have raised public awareness about legionellosis, a serious, preventable form of pneumonia that can be contracted from water systems in buildings. Legionellosis has harmed millions of people worldwide and causes annual monetary losses in the billions. However, to really understand the effects of the disease, one must listen carefully as the victims, or their survivors, describe the suffering they have endured. Preventing Legionellosis provides concise detail for: Improving awareness and education Implementing water management plans Mitigating against commercial conflict of interest The book will give the scientific basis for the worldwide technical consensus on the prevention of legionellosis. It will be an invaluable source of information for public health administrators, epidemiologists, infection control professionals, facility safety managers, industrial hygienists, and academic engineers and scientists.
Keywords: Microbiology.; elektronické knihy; electronic books